The STRIPAK Complex Regulates Response to Chemotherapy Through p21 and p27 - Rodriguez-Cupello, Carmen; Dam, Monica; Serini, Laura; Wang, Shan; Lindgren, David; Englund, Emelie; Kjellman, Pontus; Axelson, Håkan; García-Mariscal, Alberto; Madsen, Chris D. (Frontiers in Cell and Developmental Biology, 2020)
The STRIPAK complex has been linked to a variety of biological processes taking place during embryogenesis and development, but its role in cancer has only just started to be defined. Here, we expand on previous work indicating a role for the scaffolding protein STRIP1 in cancer cell migration and metastasis. We show that cell cycle arrest and decreased proliferation are seen upon loss of STRIP1 in MDA-MB-231 cells due to the induction of cyclin dependent kinase inhibitors, including p21 and p27. We demonstrate that p21 and p27 induction is observed in a subpopulation of cells having low DNA damage response and that the p21high/γH2AXlow ratio within single cells can be rescued by depleting MST3&4 kinases. While the loss of STRIP1 decreases cell proliferation and tumor growth, cells treated with low dosage of chemotherapeutics in vitro paradoxically escape therapy-induced senescence and begin to proliferate after recovery. This corroborates with already known research on the dual role of p21 and indicates that STRIP1 also plays a contradictory role in breast cancer, suppressing tumor growth, but once treated with chemotherapeutics, allowing for possible recurrence and decreased patient survival.